Pengaruh Penggunaan Abu Vulkanik Gunung Sinabung Sebagai Bahan Subtitusi Parsial Semen Terhadap Kuat Tekan dan Daya Serap Air Mortar - Widayanto Widayanto; Mizanuddin Sitompul (Portal: Jurnal Teknik Sipil, 2021)
This research aims to find out the effect of the use of volcanic ash mount Sinabung on the compressive strength and absorption of mortar and its feasibility for the manufacture of solid concrete bricks and paving blocks that meet the quality standards of building materials in Indonesia. The study was conducted by making a test object in the form of a mortar cube measuring 5x5x5 cm with variations in the composition of volcanic ash as a cement substitution material is 0%, 3%, 6%, 9%, 12%, and 15% against the initial weight of cement, and the cement-water factor is 0.60. Compressive strength and mortar water absorption test is carried out at the age of 28 days. The results showed that the factor of using volcanic ash mount Sinabung as a cement substitution material in mortar with a percentage of 0%, 3%, 6%, 9%, 12%, and 15% had a very real effect on the compressive strength and water absorption of mortar. The greater the percentage of volcanic ash the lower the mortar compressive strength and the higher the absorption of water